Clinical evaluation of low-level laser therapy and fluoride varnish for treating cervical dentinal hypersensitivity - Corona, Silmara Aparecida Milori [UNESP]; Do Nascimento, T. N.; Catirse, ABE; Lizarelli, RFZ; Dinelli, W.; Palma-DIBB, R. G. (Blackwell Publishing, 2003)
The aim of this study was to evaluate in vivo the use of low-level galium-aluminium-arsenide (GaAlAs) (BDP 600) laser and sodium fluoride varnish (Duraphat((R))) in the treatment of cervical dentine hypersensitivity. Twelve patients, with at least two sensitive teeth were selected. A total of 60 teeth were included in the trial. Prior to desensitizing treatment, dentine hypersensitivity was assessed by a thermal stimulus and patients' response to the examination was considered to be a control. The GaAlAs laser (15 mW, 4 J/cm(2)) was irradiated on contact mode and fluoride varnish was applied at cervical region. The efficiency of the treatments was assessed at three examination periods: immediately after first application, 15 and 30 days after the first application. The degree of sensitivity was determined following predefined criteria. Data were submitted to analysis and no statistically significant difference was observed between fluoride varnish and laser. Considering the treatments separately, there was no significant difference for the fluoride varnish at the three examination periods, and for laser therapy, significant difference (P < 0.05) was found solely between the values obtained before the treatment and 30 days after the first application. It may be concluded that both treatments may be effective in decreasing cervical dentinal hypersensitivity. Moreover, the low-level GaAlAs laser showed improved results for treating teeth with higher degree of sensitivity.
Keywords: Low-level GaAlAs laser; Fluoride varnish; Cervical dentine hypersensitivity